Determination of the water quality and carrying capacity of prawn farming area : a case study of the Sg Ketup catchment area of Tambirat, Samarahan Division, Sarawak - Tan, Gerald Lok Sien. (Universiti Malaysia Sarawak (UNIMAS), 2002)
The carrying capacity of the Sg. Ketup catchment as a prawn farming area in the Samarahan Division was determined. The carrying capacity stucy looked specifically at the nitrate nitrogen concentrations in the water of Sg Ketup as an indicator to approximate the possible level at which hypernutrification od the water, and hence eutrophication would occur.